THE TEACHER’S ROLE IN INSTILLING STUDENTS’ DISCIPLINE AT SDN CIOMAS 1 - Neng Sofah; Damanhuri; Ana Nurhasanah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study was to describe the teacher's role in instilling disciplined character in grade IV students at SDN Ciomas 1 Kabupaten Serang. The method in this research was the descriptive qualitative method, a series of activities to obtain data as they were without being under certain conditions, the results of which emphasized meaning. The population or the social situation consisted of three elements, namely places, actors, and activities that interacted in synergy. The data were collected through observation, interviews, and documentation. The results of this study indicated that the teacher's role at SDN Ciomas 1 Kabupaten Serang in instilling the students' discipline at grade IV was good. Students who committed disciplinary violations were relatively small since the teacher gave punishments to those students. The factors that caused undisciplined participants came from the students themselves, their peers both in the school environment and those outside the school, and influences from parents and teachers as a result of the lack of classroom mastery and good teaching methods. Thus, it was concluded that the teacher's role was very important in instilling the students' discipline, for example, by providing a good example to his students. When students violated the rules or were not disciplined, the teacher gave educative punishments.